MUSEU DE ARTE CONTEMPORÂNEA DE MATO GROSSO DO SUL (MARCO): UMA ANÁLISE SEMIÓTICA, POR MEIO DE UMA PERSPECTIVA DECOLONIAL, DE TEMPORADAS DE EXPOSIÇÕES - CACIANO SILVA LIMA (2023)
Museums are spaces for building stories and memories, not just memories and narratives told pragmatically,but showing a place of culture, teaching and learning practice. In this sense, the present study aimed to analyze the semiotic process that occurs in educational paths in the context of the Museum of Contemporary Art of Mato Grosso do Sul (MARCO). Thus, having as an epistemological basis the Greimasian semiotics (1975), under a bias of Mignolo’s decolonial perspective (2017), it sought to reflect the educational process mediated by Art Educators visitors of the museum space, under a cutout of the Museum Exhibition Seasons, exhibited in 2017. The methodology applied was a qualitative research, as it considered the literature, visions, experiences and expectations in the midst of the social contexts in which they are inserted. In this sense, the four seasons are approached and specifically the work “ Pedophilia”, by the visual artist Ropre, present in the Cadafalso exhibition, of the Third Season of Exhibitios which was the object of censorship. It sought to understand in the artistic language of the work the portray of contemporary issues against these violence, the visual identity of the artist's exhibition and the construction of her works, loaded with discourses, necessary for deconstructions within society. Finally, considerations are made about the role of Art Education, as a guiding thread to transform society and improve interpersonal and transpersonal relationships, promoting the strengthening of identities, which spreads and preserves the marks left by time. Keywords: MARCO. Semiotic. Decoloniality. Art Education.